Toward a clinical model for patient spiritual journeys in supportive and palliative care: Testing a concept of human spirituality and associated recursive states. Issue 1 (February 2021) - Johnson, Rebecca; Hauser, Joshua; Emanuel, Linda
Abstract: Objective: In 2015, a Chaplaincy Research Consortium generated a model of human spirituality in the palliative care context to further chaplaincy research. This article investigates the clinical fit of (a) the model's fundamental premise of universal human spirituality and (b) its 4 proposed stage descriptors ( Discovery, Dialogue, Struggle, and Arrival ). Method: First, we collected qualitative data from an interdisciplinary palliative care focus group. Participants ( n = 5) shared responses to the statement "the human spirit has essential commonalities across [ … ] groups and [ … ] attributes. " Participants also shared vignettes of spiritual care, and 48 vignettes illustrating patients' spiritual journeys were subsequently taken from the transcript of that group. Second, we invited different mixed discipline palliative care professionals ( n = 9) to individually card sort these vignettes to the model's 4 stage descriptors; we conducted pattern analysis on the results. We then administered a third step, convening six physicians to complete the card sort again, this time allowing designation of cards to one or two of the 4 stage descriptors. Results: Focus group participants were supportive of the model's all-encompassing definition of spirituality. The concept of "connectedness" was a shared focus for all participants, connectedness and spirituality appearing almost synonymous. Pattern analysis of assigned 48 vignettes to the 4 stages showed stronger consensus around Discovery and Arrival than Struggle and Dialogue . Results of the additional card sort suggested Struggle and Dialogue involve oscillation and are harder to think of as a steady state as distinct from processes associated with Discovery or Arrival . Significance of results: "Connectedness" is a productive concept for modeling human spiritual experience near the end of life. As one healthcare professional said: "this connectedness piece is [ … ] what I always look for … " Although further work is needed to understand struggle and dialogue elements in peoples' spiritual journeys, discovery and arrival shared consensus among participants.